2015
DOI: 10.1007/s00049-015-0188-3
|View full text |Cite
|
Sign up to set email alerts
|

Bacteria may enhance species association in an ant–aphid mutualistic relationship

Abstract: The mutualistic relationships between certain ant and aphid species are well known, the primary benefits being protection for the aphids and carbohydrate-rich honeydew for the ants. Questions remain, however, as to the exact semiochemical factors that establish and maintain such relationships. In this study, we used a series of treatments and associated controls placed at the end of a two-way olfactometer to determine the degree of attractiveness of a complete plant-aphid-honeydew system as well as individual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
52
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(55 citation statements)
references
References 52 publications
2
52
0
Order By: Relevance
“…However, in order to assess these criteria, ant foragers must already have found the aphid colony. Previous studies already showed ants ability to orient their search for aphid colonies using volatile cues (Verheggen et al ., ; Fischer et al ., ). The data presented here is the first evidence of distant aphid species discrimination by ants that is driven by aphid honeydew and mediated by the associated microflora through release of VOCs, in laboratory conditions.…”
Section: Discussionsupporting
confidence: 73%
See 4 more Smart Citations
“…However, in order to assess these criteria, ant foragers must already have found the aphid colony. Previous studies already showed ants ability to orient their search for aphid colonies using volatile cues (Verheggen et al ., ; Fischer et al ., ). The data presented here is the first evidence of distant aphid species discrimination by ants that is driven by aphid honeydew and mediated by the associated microflora through release of VOCs, in laboratory conditions.…”
Section: Discussionsupporting
confidence: 73%
“…Moreover, this tendency is supported by the relative attractiveness of honeydews and bacterial cultures issued of these 2 aphid species, confirming both ants ability to distantly discriminate between 2 aphid species, and honeydew VOCs involvement in that discrimination. Even though mVOCs emitted from honeydew have been reported to attract aphid enemies and potential ant partners (Leroy et al ., ; Fischer et al ., ), this is the first evidence of ant ability to use such volatile cues to distantly discriminate 2 aphid species. Furthermore, the attractiveness shown by Acyrthosiphon pisum when presented alone, strongly reduced when Aphis fabae is added in the possible choices, suggests that ants might adapt their response depending on available resources.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations